Peningkatan Hasil Belajar Matematika Materi Ruas Garis Menggunakan Media Audio Visual pada Peserta Didik SD - Sulistiani, Rochmani Diah (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve student learning outcomes in the material of finding line segments in Mathematics. This research is a Classroom Action Research (PTK) which was conducted in 3 cycles. Each cycle consists of planning, implementing, observing and reflecting. The subjects of this study were students of class II SD Negeri Kebonkliwon in the 2020/2021 academic year, totaling 27 students. Data collection techniques using test and non-test techniques. The assessment instrument uses item - item and observation rubric assessment. Analysis of the data used in the study included a comparative descriptive technique, namely statistical techniques by comparing the scores between cycles, the mean, the minimum score, the maximum and the percentage. The results showed that the use of audio-visual media can improve student learning outcomes in Mathematics subject matter on line segment material. This is evidenced by the learning outcomes in cycle I, namely 9 students out of 27 students or 33% who have not completed, while 18 students out of 27 students who have completed it or 67%. In cycle II, there were 7 students who had not completed, 27 or 26%, while 20 out of 27 students or 74% had finished. This means that student learning outcomes increase from cycle I to cycle II. The conclusion of this study is that the use of audio-visual media can improve mathematics learning outcomes in line segment material in class II SD Negeri Kebonkliwon students.